Integrating Soil Parameter Uncertainty into Slope Stability Analysis: A Case Study of an Open Pit Mine in Hungary - Petra Oláh; Péter Görög (Geosciences, 2025)
This study presents a probabilistic geotechnical analysis of the Visonta Keleti-III lignite mining area, focusing on the statistical evaluation of soil parameters and their integration into slope stability modeling. The objective was to provide a more accurate representation of the spatial variability of geological formations and mechanical soil properties in contrast to traditional deterministic approaches. The analysis was based on over 3300 laboratory samples from 28 boreholes, processed through multi-stage outlier filtering and regression techniques. Strong correlations were identified between physical soil parameters—such as wet and dry bulk density, void ratio, and plasticity index—particularly in cohesive soils. The probabilistic slope stability analysis applied the Bishop simplified method in combination with Latin Hypercube simulation. Results demonstrate that traditional methods tend to underestimate slope failure risk, whereas the probabilistic approach reveals failure probabilities ranging from 0% to 46.7% across different sections. The use of tailored statistical tools—such as Python-based filtering algorithms and distribution fitting via MATLAB—enabled more realistic modeling of geotechnical behavior. The findings emphasize the necessity of statistical methodologies in mine design, particularly in geologically heterogeneous, multilayered environments, where spatial uncertainty plays a critical role in slope stability assessments.